Can Foreign investment Accelerate Economic Growth in Cen-tral Java? Empirical Evidences from 15 Regencies and Cities Data - Muhammad Raid Ardel; Al Muizzuddin Fazaalloh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research aims to analyze the impact of foreign investment (PMA) on economic growth in Central Java Province. Comprehensive and sustainable development efforts in Central Java have brought economic progress to its people. However, these development achievements have not yet reached their maximum potential. In this case, the processing industry sector is one of the most influential basic sectors in Central Java from 2010 to 2022. This research uses secondary data from the Central Statistics Agency (BPS) and the Investment Coordinating Board (BKPM) for the 2010-2022 period. The analytical method used is Generalized Method of Moments (GMM) dynamic panel data regression analysis to evaluate the relationship between FDI and economic growth as measured by Gross Regional Domestic Product (GRDP). Control variables such as Number of labors, Government Consumption Expenditures, and Mediation Variables namely Average Years of Schooling are also included in the model to obtain more accurate results. The results show that FDI has a positive and significant influence on GRDP, supported by innovation, technology transfer and productivity. The interaction between FDI and education is also significant, indicating the importance of labor quality in maximizing the benefits of foreign investment. The average length of independent schooling also has a significant impact on GRDP. In addition, government consumption expenditure and labor play a positive role as supporting factors, encouraging inclusive and sustainable economic growth.